(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines methods and technologies for developing creative thinking in extracurricular club activities. It focuses on creative pedagogy and interactive, student-centered approaches that promote independent thinking and innovative problem-solving. Methods such as debates, brainstorming, mind mapping, and project-based learning are presented as effective tools for fostering creativity. The study emphasizes that well-structured and technology-supported club activities create favorable conditions for developing creative and socially active learners.